#1**0 **

Solve the following system:

{5 x - 4 y = -4 | (equation 1)

2 x - 4 y = -16 | (equation 2)

Subtract 2/5 × (equation 1) from equation 2:

{5 x - 4 y = -4 | (equation 1)

0 x - (12 y)/5 = (-72)/5 | (equation 2)

Multiply equation 2 by -5/12:

{5 x - 4 y = -4 | (equation 1)

0 x+y = 6 | (equation 2)

Add 4 × (equation 2) to equation 1:

{5 x+0 y = 20 | (equation 1)

0 x+y = 6 | (equation 2)

Divide equation 1 by 5:

{x+0 y = 4 | (equation 1)

0 x+y = 6 | (equation 2)

**x = 4 and y = 6**

Guest Sep 19, 2019

#2**+2 **

Multiply first equation by - 1 to get

-5x+4y=4 add this to the second equation to get

-3x=-12 so x = 4

Substitute this value of 'x' in to one of the equations to get 'y'

5(4)-4y = -4

20-4y =-4

-4y = -24 y = 6

ElectricPavlov Sep 19, 2019